Vlogger and Brand Credibility Perception: A Systematic Literature Review of Endorsement Effectiveness in Youtube Vlogs - Ina Nafilla Zahrah (Jurnal Indonesia Sosial Teknologi, 2024)
The presence of online celebrities, such as YouTube vloggers, has made online marketing efforts through endorsements even easier. This study analyses the effectiveness of endorsements on YouTube vlogs (video blogs) by assessing the perceived credibility of vloggers and brands. The research was carried out through the systematic literature review method by following various stages in the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) model. Of the 16 available articles, 4 journal articles were produced, which discussed in detail the effectiveness of endorsements on YouTube vlogs to perceptions of vloggers and brand credibility. The results of this study show that the endorsement's effectiveness is closely related to the vlogger's perceived credibility while also impacting the endorsement product. Overall, understanding the effectiveness of endorsements on YouTube vlogs can help companies choose the right vloggers and achieve marketing success.